2018
DOI: 10.1002/uog.18838
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free fetal DNA analysis in maternal plasma as screening test for trisomies 21, 18 and 13 in twin pregnancy

Abstract: In twin pregnancy without fetal ultrasound abnormality, cfDNA screening for trisomies 21, 18 and 13 had a high success rate and good performance. Therefore, in routine practice, cfDNA analysis could be considered as a first- or second-line screening test. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…The search identified 329 potentially relevant citations, but 322 were excluded because they were non-relevant publications, conference abstracts rather than peer-reviewed papers, review articles or opinions, studies not on twins, case-control studies, or studies on clinical implementation of cfDNA testing in screening for aneuploidies in which pregnancy outcome data were provided for fewer than 85% of the study population, proof-of-principle studies reporting laboratory techniques rather than clinical validation of a predefined method of maternal blood cfDNA analysis (Figure 1). In total, 9 relevant studies were identified 4,5,[17][18][19][20][21][22][23] but two of these 4,5 were excluded from the meta-analysis because their data are included in the updated Fetal Medicine Foundation results presented above. The characteristics of our current study and the seven ones identified by the literature search are summarized in Table 1.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The search identified 329 potentially relevant citations, but 322 were excluded because they were non-relevant publications, conference abstracts rather than peer-reviewed papers, review articles or opinions, studies not on twins, case-control studies, or studies on clinical implementation of cfDNA testing in screening for aneuploidies in which pregnancy outcome data were provided for fewer than 85% of the study population, proof-of-principle studies reporting laboratory techniques rather than clinical validation of a predefined method of maternal blood cfDNA analysis (Figure 1). In total, 9 relevant studies were identified 4,5,[17][18][19][20][21][22][23] but two of these 4,5 were excluded from the meta-analysis because their data are included in the updated Fetal Medicine Foundation results presented above. The characteristics of our current study and the seven ones identified by the literature search are summarized in Table 1.…”
Section: Data Sourcesmentioning
confidence: 99%
“…In singletons, the sensitivity of cfDNA screening for trisomy 21 is 99%, with a FPR less than 0.02%. [10] While there is still limited data available for performance of cfDNA screening in twins, and relatively no data for higher order multiples, in 10 published twin cohorts [2332] the sensitivity for trisomy 21 was 92–100% with a FPR less than 0.5%. The improved sensitivity and lower FPR of cfDNA screening for Trisomy 21, compared to conventional screening in multiple gestation pregnancies, positions cfDNA as a valuable screening alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the occurrence of no results with the Harmony TM Prenatal Test was more pronounced in the subgroup of patients with IVF, while there was no difference between the 2 subpopulations of patients with the mother's weight ≥80 kg, who typically have a higher proportion of patients with a lower FF. Previous studies on singleton and twin pregnancies have shown that the GW-MPS method by Cerba testing leads to comparable no-result rates between IVF and non-IVF patients, whereas studies on singleton and twin pregnancies using the DANSR method showed a clearly significant difference in terms of no-result rates for IVF patients [4,16,27,28]. The increase in no-result rate with the DANSR method is not solely explained by a lower FF in this group.…”
Section: Uninformative Cfdna Testingmentioning
confidence: 59%